Meter-Scale 3D Seismic Data for High-Resolution Site Characterization - Lebedeva-Ivanova, Nina; Polteau, Stephane; Zastrozhnov, Dmitry; Planke, Sverre; Waage, Malin; Bünz, Stefan; Bellwald, Benjamin; Vanneste, Maarten; Sauvin, Guillaume; Myklebust, R. (81st EAGE Conference and Exhibition 2019, 2019)
Source at https://10.3997/2214-4609.201901933 . High-resolution 3D site characterization can deliver reliable quantitative property volumes of the subsurface when based on seismic data able to image meter-sized objects. Following the theoretical analysis of seismic wave propagation in the shallow sub-surface, we present case studies based on re-processing of 3D P-Cable seismic data. The case study of data re-processing from the Vestnesa Ridge west of Svalbard and the outer Vøring Basin show that P-Cable 2.5D and 3D data can provide decimeter- to meter-scale vertical resolution of the shallow subsurface. Collection of new 3D P-Cable data with optimized acquisition parameters will provide meter-scale horizontal and vertical resolution. Therefore, 3D seismic volumes will represent the framework for data interpretation, integration and inversion where in situ measurements can be propagated with minimal data interpolation.